2001
DOI: 10.1042/bss0670023
|View full text |Cite
|
Sign up to set email alerts
|

The role of post-translational modification in ϐ-amyloid precursor protein processing

Abstract: The ϐ-amyloid precursor protein (APP) plays a pivotal role in the early stages of neurodegeneration associated with Alzheimer's disease. An alteration in the processing pattern of the protein results in an increase in the generation of the 40-42-amino-acid ϐ-amyloid (Aϐ) peptide, which coalesces to form insoluble, extracellular amyloid deposits. A greater understanding of the factors that influence APP processing may assist in the design of effective therapeutic agents to halt progression of Alzheimer's diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 65 publications
(82 reference statements)
0
28
0
1
Order By: Relevance
“…An interference of post-translational modifications with APP processing has been reported previously (Tomita et al, 1998;Galbete et al, 2000;Georgopoulou et al, 2001). The processing of human APP in transgenic flies lacking BACE leads to the generation of a slightly larger peptide, ␦-A␤, by cleavage aminoterminally to the usual ␤-cleavage site.…”
Section: Discussionmentioning
confidence: 94%
“…An interference of post-translational modifications with APP processing has been reported previously (Tomita et al, 1998;Galbete et al, 2000;Georgopoulou et al, 2001). The processing of human APP in transgenic flies lacking BACE leads to the generation of a slightly larger peptide, ␦-A␤, by cleavage aminoterminally to the usual ␤-cleavage site.…”
Section: Discussionmentioning
confidence: 94%
“…Glycosylation, particularly sialylation, of APP has been proposed to influence the processing pathway of APP by determining its passage from the Golgi to the cell membrane (50,71,72). Additionally, a study by Tomita et al (73) concluded that APP is only cleaved after maturation by O-glycosylation, which occurs during the transport of APP through the Golgi complex.…”
Section: Discussionmentioning
confidence: 99%
“…23 CK2 can also phosphorylate E-cadherin and the disruption of the adherens junction is associated with a decreased phosphorylation of E-cadherin by CK2. 24 Interestingly, the only other type I ectoprotein that is reported to be regulated by CK2 is the CD10/neutral endopeptidase 24,11,25 which also plays a key role in the degradation of bradykinin in endothelial cells. 26 Although PKC has been reported to associate with testis ACE, 27 we were unable to detect any such association in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…8 The cleavage/secretion of testis ACE is reported to be a regulated process that can be stimulated by phorbol 12-myristate 13-acetate (PMA), 9 a property that ACE shares with other ectoproteins such as tumor necrosis factor-␣ 10 and ␤-amyloid precursor protein. 11 Apart from the fact that somatic ACE is less efficiently cleaved than testis ACE, 7,12 and that ACE shedding is sensitive to metalloprotease inhibitors, 13,14 little or nothing is known about the mechanisms controlling the cleavage/secretion of somatic ACE from endothelial cells.…”
mentioning
confidence: 99%